Pixel DAQ and trigger for HL-LHC. (10th March 2017) - Morettini, P.
Abstract: The read-out is one of the challenges in the design of a pixel detector for the High Luminosity upgrade of the Large Hadron Collider (HL-LHC), that is expected to operate from 2026 at a leveled luminosity of 5 × 10 34 cm −2 s −1 . This is especially true if tracking information is needed in a low latency trigger system. The difficulties of a fast read-out will be reviewed, and possible strategies explained. The solutions that are being evaluated by the ATLAS and CMS collaborations for the upgrade of their trackers will be outlined and ideas on possible development beyond HL-LHC will be presented.